Postcards from the edge - Fisher, Carrie (Simon & Schuster Paperbacks, 2010)
When we first meet the extraordinary young actress Suzanne Vale, shes feeling like "something on the bottom of someones shoe, and not even someone interesting." Suzanne is in the harrowing and hilarious throes of drug rehabilitation, trying to understand what happened to her life and how she managed to land in a "drug hospital."